ASPEK YURIDIS PENYERAHAN WEWENANG DARI PEMERINTAH PUSAT KEPADA PEMERINTAH DAERAH DALAM HAL PELAKSANAAN OTONOMI DAERAH - Sidi Purnama, I Gede; Ariani, I Gusti Ayu Agung (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
Indonesia is unitary states that have principle of decentralization in governance byproviding the opportunity and freedom to the region to conduct the regional autonomy. Inthe transfer of authority from central government to local governments (decentralization)required of consideration or criteria to hand over the authority to administer and managethe affairs of government, in accordance with the regulations. But in practice usually theprocess of authority transfers was not based on existing regulations. The Issues to bediscussed is about how the authority can be determined the affairs of the centralgovernment to the local government and what are the criteria for transfer of authority fromcentral government to local governments. The method used in this research is thenormative study. From the results of this study indicate that local governments cannot denythe required government’s affairs. And the criteria in the transfer of authority fromcentral government to local governments is just if the matters are more efficient andeffective if implemented by local governments.
Keywords: Government, Autonomy, Rules, Authority.